(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2024)
In forensic science, soil as trace evidence can play a vital role of establishing connection between the suspect, victims, any object with a particular area based on the characteristics of soil. Forensic soil investigation is the analysis of soil evidence in the service of crime solving, environmental monitoring, and geologic exploration. Analysts use a combination of geological, ecological, biological, or chemical methods to identify soil origin, link evidence to crime scenes, or reconstruct events. This study aims to conduct a comprehensive review of existing literature on soil as trace evidence, with a focus on its forensic applications. This covers various aspects of forensic soil investigation, including Physical methods (grain size analysis, density gradient measurement), chemical processes (organic matter analysis; loss on ignition (LOI), pH), biological methods (DNA analysis, microbial community analysis), and mineralogical analysis (SEM-EDX, XRD), For soil analysis, these methods are evaluated for their applicability and limitations. It concludes by arguing the importance of assembling multiple disciplines for effective forensic soil investigation. It provides a helpful resource for forensic scientists and researchers, as well as for investigators and practitioners in forensic science.